Historiography and self-definition : Josephos, Luke-Acts, and apologetic historiography - Sterling, Gregory E. (Novum Testamentum, Supplements, 1992)
For centuries scholars have recognized the apologetic character of the Hellenistic Jewish historians, Josephos, and Luke-Acts; they have not, however, adequately addressed their possible relationships to each other and to their wider cultures. In this first full systematic effort to set these authors within the framework of Greco-Roman traditions, Professor Sterling has used genre criticism as a method for locating a distinct tradition of historical writing, apologetic historiography. Apologetic historiography is the story of a subgroup of people which deliberately Hellenizes the traditions of the group in an effort to provide a self-definition within the context of the larger world. It arose as a result of a dialectic relationship with Greek ethnography. This work traces the evolution of this tradition through three major eras of eastern Mediterranean history spanning six hundred years: the Persian, the Greek, and the Roman.